The Effect of Antenatal Yoga on Lower Back Pain in Third-Trimester Pregnant Women at Ertitawati Siregar's Independent Midwifery Practice in Olora Village, Gunungsitoli City - Desi Handayani Lubis; Sri Rezeki; Erin Padilla Siregar; Pratiwi Lumbantobing (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Pregnancy-related low back pain (LBP) is prevalent in late gestation and can negatively affect physical comfort and psychological well-being. Non-pharmacological interventions such as antenatal yoga are increasingly incorporated into routine care; however, pragmatic evidence from community-based settings remains limited. This study examined within-subject changes in LBP severity among third-trimester pregnant women participating in a structured antenatal-yoga program delivered at a community midwifery clinic. Researchers conducted a single-group pre-experimental pretest-posttest study at an independent midwifery clinic in Gunungsitoli, Indonesia. Forty pregnant women ≥28 weeks' gestation were recruited through purposive sampling. The intervention consisted of supervised prenatal-yoga sessions held three times per week over four weeks. Pain intensity was assessed before and after the program using the Numeric Rating Scale (NRS) and categorical severity bands (mild, moderate, severe). Pre-post differences were analysed using the Wilcoxon signed-rank test. Participation in antenatal yoga was associated with a clinically meaningful reduction in pain severity. Prior to the intervention, 62.5% of participants reported moderate pain and 37.5% reported mild pain; no cases of severe pain were observed. Following the intervention, 82.5% reported mild pain and 17.5% reported moderate pain. The change in NRS scores was statistically significant (p < 0.001). In this pragmatic third-trimester cohort, engagement in a structured antenatal yoga program was linked to reduced LBP severity and a shift toward milder pain categories. These findings support the feasibility of integrating antenatal yoga into routine prenatal care as a non-pharmacological option. Future controlled studies incorporating effect sizes, confidence intervals, functional outcomes, adherence andsafety monitoring, and short-term follow-up are recommended to strengthen casual inference and inform optimal program design. Keywords: Antenatal Yoga, Pregnancy, Third Trimester, Low Back Pain, Non-Pharmacological Intervention, Community Midwifery, Pretest-Post-test.